Generation Z Attitude towards Domestic Tourism in KwaZulu-Natal, South Africa: Array - Aina, Anita O.; Ezeuduji, Ikechukwu O. (Acta Universitatis Danubius. Œconomica, 2022)
The purpose of this study is to explore KwaZulu-Natal Generation Z members’ attitude towards domestic tourism in South Africa. The study was conducted in four major towns in KwaZulu-Natal Province of South Africa, namely: Durban, Pietermaritzburg, Richards Bay, and St. Lucia. A structured questionnaire survey of 385 respondents was used to generate data for analysis. Results show that KwaZulu-Natal Generation Z members portray positive attitude towards domestic tourism in South Africa. They are loyal to their destination brand. However, limited funds mostly deter KwaZulu-Natal Generation Z members from getting involved in domestic tourism activities. Results also show that they mostly rely on social media and other forms of technology, to source information pertaining to domestic tourism activity planning and reviewing. This study recommends that competitive pricing of domestic tourism activities (through reduced operational costs and bundle pricing) should be encouraged especially during peak seasons, as majority of Generation Z domestic tourists have difficulties to afford travel costs. Furthermore, the study recommends the creation of intensive and incessant awareness of KwaZulu-Natal domestic tourism sites through numerous platforms such as social media, movies, music videos and also personal referrals, enabling a wider reach to the Generation Z members.